Estimating the Rate of Cessation of Magnetospheric Activity in AMPERE Field‐Aligned Currents. Issue 23 (13th December 2018) - Moretto, T.; Hesse, M.; Vennerstrøm, S.; Tenfjord, P.
Abstract: The decay of magnetospheric activity when driving is turned off (to a minimum) was measured in total field‐aligned current estimates from the Active Magnetosphere and Planetary Electrodynamics Response Experiment (AMPERE) project. Events of distinct northward turnings of the interplanetary magnetic field were identified, with prolonged periods of stable southward driving conditions followed by northward interplanetary magnetic field conditions. All but 4 of 43 identified events exhibit a well‐defined exponential decay in the total hemispheric field‐aligned current following the northward turning. A superposed epoch analysis yields a generic decay constant of 0.9, corresponding to an e ‐folding time of 1.1 hr. A statistical analysis of the ensemble of events also reveals a seasonal variation in the decay parameter with faster decay observed in the winter than in the summer hemisphere. This result can be understood in terms of stronger/weaker line tying of the ionospheric foot points of magnetospheric field lines for higher/lower conductivity. Plain Language Summary: Energy and circulation in the Earth's magnetosphere and ionosphere are largely determined by conditions in the solar wind and interplanetary magnetic field. When the driving from the solar wind is turned off, we expect the activity to die down but how this happens is not known. With newly available data from a large constellation of satellites we can get a measure of the global activity level. These observations show that the activity decays exponentially with a generic decay time of 1.1 hr. This finding indicates a fundamental behavior of the magnetosphere‐ionosphere system, which is crucial to fully understand its dynamics. Key Points: Magnetospheric activity exhibits approximate exponential decay when solar wind driving is turned off (minimized) An average exponential time constant of 1.1 hr is measured in total hemispheric field‐aligned current estimates Longer decay time is observed in the summer compared to the winter hemisphere, consistent with expectations for ionospheric line tying